Guidelines for authors-English Version - NA, NA (Universidad Santo Tomás / Instituto Colombiano de Normas Técnicas y Certificación ICONTEC, 2016)
Journal SIGNOS “Investigación en sistemas de gestión” aims to serve as a means of dissemination for reflections, discussions and findings on issues related to management systems and social responsibility, as well as experiences related to the applicability, innovation and relevance of theories, models and management systems in private and public organizations.